Representation of Family Values in Wardah Ramadan Series YouTube Channel: Peirce Semantic Analysis Study on Mengalah untuk Melangkah Web Series - Nanik Mujiati,; Dwi Ubaidillah Hidayat,; Galuh Nuril Lathifah, (Kediri Journal of Journalism and Digital Media (KJOURDIA), 2025)
This research aims to understand the representation of family values in the web series titled "Mengalah untuk Melangkah" which aired on the Wardah Ramadan Series YouTube channel in Ramadan 2025. This series has attracted the attention of YouTube users with 4.2 million views. The research method used is descriptive qualitative research with Charles Sanders Peirce semiotic analysis technique. The Charles Sanders Peirce analysis technique applied in this study consists of three aspects known as the triadic structure: Reprecentamen (sign), Interpretant, and Object. The results showed that there is a representation of family values in the web series “Mengalah untuk Melangkah” including, preventing sin, helping family members, fostering cooperation, respecting the family, a sense of attention, compassion, responsibility and mutual help, as well as understanding and supporting the decisions of family members.